Northeast Public Sector Forum - George, Cal (Tufts Archival Research Center, 2007)
Memo discussing Tobacco Institute meeting with the Northeast AFL-CIO Council. Lists union officials present. Includes packet of fair tax briefing materials detailing labor's recent action in support of fair taxes. Attached is a statement by the AFL-CIO Executive Council on taxes and the defecit which asks for an income tax and opposes excise taxes. Also includes article from AFL-CIO News discussing protection of the social security trust fund.